Vav1 Fine Tunes p53 Control of Apoptosis versus Proliferation in Breast Cancer - Sebban, Shulamit (Public Library of Science, 2013)
Vav1 functions as a signal transducer protein in the hematopoietic system, where it is exclusively expressed. Vav1 was recently implicated in several human cancers, including lung, pancreatic and neuroblasoma. In this study, we analyzed the expression and function of Vav1 in human breast tumors and breast cancer cell lines. Immunohistochemical analysis of primary human breast carcinomas indicated that Vav1 is expressed in 62% of 65 tumors tested and is correlated positively with estrogen receptor expression. Based on published gene profiling of 50 breast cancer cell lines, several Vav1-expressing cell lines were identified. RT-PCR confirmed Vav1 mRNA expression in several of these cell lines, yet no detectable levels of Vav1 protein were observed due to cbl-c proteasomal degradation. We used two of these lines, MCF-7 (Vav1 mRNA negative) and AU565 (Vav1 mRNA positive), to explore the effect of Vav1 expression on breast cell phenotype and function. Vav1 expression had opposite effects on function in these two lines: it reduced proliferation and enhanced cell death in MCF-7 cells but enhanced proliferation in AU565 cells. Consistent with these findings, transcriptome analysis revealed an increase in expression of proliferation-related genes in Vav1-expressing AU565 cells compared to controls, and an increase in apoptosis-related genes in Vav1-expressing MCF-7 cells compared with controls. TUNEL and γ-H2AX foci assays confirmed that expression of Vav1 increased apoptosis in MCF-7 cells but not AU565 cells and shRNA experiments revealed that p53 is required for this pro-apoptotic effect of Vav1 in these cells. These results highlight for the first time the potential role of Vav1 as an oncogenic stress activator in cancer and the p53 dependence of its pro-apoptotic effect in breast cells.